Women's Labour Force Participation and Domestic Violence: Evidence from India. (August 2016) - Paul, Sohini
Domestic violence is recognized as a serious violation of women's basic rights. Conventional economic models of domestic violence suggest that higher labour force participation by women leads to a decrease in domestic violence. In this article, we study the relationship between women's employment and domestic violence using the ecological framework of violence developed by Heise (1998). We use a sample of 69, 704 married women aged 15–49 years from Round III of the National Family Health Survey (NFHS) data (2005–2006) for our analysis. We report a positive association between women's labour force participation and physical as well as emotional abuse by husbands: employed women are thus more exposed to intimate partner violence. However, we did not find much evidence that domestic violence resulted from a larger control of household resources by working women. We argue that the emotional cost may become high for men when household decision-making power diverges from the traditional gender norm, and men may turn to violence to restore their domestic dominance.